Avaliação da toxicidade reprodutiva da sinvastatina em Ratos machos adultos - Banzato, Thais Petrochelli [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Statins are lipid lowering agents extensively used in human clinical medical. They exert their effects through inhibition of HMG-CoA reductase, a crucial enzyme in cholesterol synthesis. Since cholesterol is the precursor of steroid hormones, drugs that decrease cholesterol may damage male reproductive function. Investigate the effects of the exposure to different doses of simvastatin on the reproductive parameters of adult male Wistar rats. Thirty rats were randomly assigned into three groups: simvastatin (20 or 40 mg/kg), control (vehicle - DMSO/oil), and were treated for 30 days orally for evaluation of reproductive parameters after euthanasia. Weight of the reproductive organs; sperm counts, motility and morphology; histopathology; hormonal levels and fertility. The weight of reproductive organs, sperm motility and histopathology analysis were similar among groups. There was a decrease in sperm production and epididymis sperm number, uterus weight with fetuses, implant and live fetuses numbers in simvastatin groups. The animals exposed to simvastatin showed an increase in the pre-implantation loss and sperm with abnormal morphology. The observed effects on reproductive parameters could be associated with toxic effects of simvastatin on spermatogenesis, causing potential damage to male fertility

As estatinas são amplamente utilizadas no tratamento da hiperlipidemia e estão entre as drogas com maiores índices de vendas no mundo. Seu efeito se dá através da inibição competitiva da HMGCoA redutase, uma enzima limitante da síntese de colesterol que catalisa a conversão de HMG-CoA em mevalonato, interrompendo a cascata da síntese do colesterol e isoprenóides. Para os ensaios in vitro de reatividade farmacológica, ratos (n = 5) foram eutanaziados e epidídimo, canal deferente, e glândula seminal foram removidos. Após isso, os tecidos foram isolados e montados em câmaras musculares para o registro digital do desenvolvimento da tensão isométrica. Foi construída uma curva concentração- resposta à noradrenalina com a sinvastatina nas concentrações 3, 10, 30 e 100 μM. Não houve alterações na sensibilidade à noradrenalina nos ductos deferente e epididimário entre os grupos. Esses resultados estão relacionados com o não comprometimento da motilidade espermática e tempo de trânsito espermático pelo epidídimo em estudo realizado com animais expostos a 20 e 40 mg/Kg/dia de sinvastatina
Keywords: Reprodução; Rato como animal de laboratorio; Toxicidade - Testes; Ensaios clínicos; Fármacos; Toxicologia experimental; Toxicity testing